Letters from Éamonn Duggan, written during the course of the Easter Rising - Duggan, Éamonn, 1874-1936; Duggan, May (1916)
Letters from Éamonn Duggan, written from Fr. Mathew Hall and for the most part sent to his fiancée May Kavanagh, in which he records his thoughts on the progress of the rebellion, the morale amongst the Volunteers in his battalion and reports of injuries and deaths amongst the ranks of the republicans. Also included are ephemeral items dating from the Rising, notably travel passes issued to Kavanagh and her friend Mrs. Morkan, dated 29 April and 1 May 1916.
Also included are travel passes, issued to Kavanagh during the Rising.
Duggan was a member of the Irish Volunteers and fought at the North Dublin Union and later Fr. Mathew Hall during the Easter Rising.
Keywords: Duggan, Éamonn, -- 1874-1936; Ireland -- History -- Easter Rising, 1916